Protection of Natural Environments in the Tundra - Khantimer,I. S. (1974)
The tundra is a rapidly developing, yet exhaustible source of a variety of natural resources, the most important of which is the vegetation cover. The natural productivity of the vegetation cover is insignificant; it decreases significantly in a south to north direction. This pattern must not serve as a justification for a negligent attitude toward exceptionally important problem's involving the balance of matter and energy in the expanses of the tundra. A concerned attitude toward the vegetation cover and its rational use are the basic prerequisite for retention of its role in the biological cycling of matter. Draft trans. of mono. Ikhrana Prirody v Zone Tundry, Leningrad, 1974 p205-207.